Effect of Ingested Fluid Composition on Exercise-related Transient Abdominal Pain - Morton, Darren Peter (2004)
The present study investigated the effect of ingested fluid composition on the experience of exercise-related transient abdominal pain (ETAP). Forty subjects, susceptible to ETAP, completed 4 treadmill exercise trials: a no-fluid trial and flavored water (FW, no carbohydrate, osmolality = 48 mosmol/L, pH = 3.3), sports drink (SD, freshly mixed Gatorade®, 6% total carbohydrate, 295 mosmol/L, pH = 3.3), and reconstituted fruit juice (FJ, BERRI® orange, 10.4% total carbohydrate, 489 mosmol/L, pH = 3.2) trials. Measures of the experience of ETAP and gastrointestinal disturbances, particularly bloating, were quantified. The FJ was significantly (p < .01) more provocative of both ETAP and bloating than all other trials. There was no difference among the no-fluid, FW, and SD in the severity of ETAP experienced, although the difference between the no-fluid and SD approached significance at the .05 level (p = .056). There was a significant relationship between both the mean (r = 0.40, p < .01) and peak (r = 0.44, p < .01) levels of ETAP and bloating. When the level of bloating was controlled for, the FJ remained significantly (p < .01) more provocative of ETAP than the other conditions, with no difference between the FW and SD (p = .37). The results indicate that in order to avoid ETAP, susceptible individuals should refrain from consuming reconstituted fruit juices and beverages similarly high in carbohydrate content and osmolality, shortly before and during exercise. Further, the mechanism responsible for the heightened experience of ETAP in the FJ trial extends beyond a gastric mass explanation.